Produzindo diferença: gênero, dualismo e transformação entre os Akw-Xerente - Clarisse Marina dos Anjos Raposo (2009)
This dissertation attempts to observe the communication processes between the poles that constitute the Akw-Xerente dualism, from a gender perspective, projecting the opposition between male and female onto other aspects of their sociality. The suggestion is that the communication processes are many times played by the women, who act as operators of a disjunctive synthesis between identity and otherness. By considering the gender relations established by the Akw-Xerente, the analysis intends to raise important issues about what it means to be different and to be equal and about the administration of equality and difference involved in the construction of the human. The line of reasoning led to the conclusion that Akw-Xerente dualism acts both as an operator opening the socius, and as a mechanism of anti-totalization. This peculiarity posits a problem to frame the Akw-Xerente into the Gê classic model, supported by the dichotomy between center and periphery and the image of these groups as self-reproductive wholes.